Empowering students’ agentive engagement through formative assessment in online learning environment - Zohre Mohammadi Zenouzagh; Wilfried Admiraal; Nadira Saab (International Journal of Educational Technology in Higher Education, 2025)
Abstract This study investigated empowering students to engage agentively in formative assessment of their English writing. To this end, student agentic engagement was explored drawing on multiple data collection. A Digitalized Engagement Enhancement Tool (DEET) was utilized to encourage students to record, unpack, plan for actions, and reflect on the feedback they received from the teacher and their peers. A series of content analyses was conducted to codify and track students’ engagement dimensions and practices in multiple writing samples, DEET, and student-revised sample writings. The analysis of the frequency of student engagement codes and their writing performances indicated a significant increase in student engagement at all dimensions. Further Chi-square analysis indicated that student agentic engagement was characterized by reciprocal and proactive practices in the critical assessment of their writing. The analyses indicated significant increase in the quality of student writing performances as well. Thematic analysis of students’ evaluation of self-perceived efficacy of DEET provided insights for teaching practitioners to build on the formative purpose of student engagement enhancement practices. The implications for teaching practitioners were discussed.